An overview of the cognitive theory and treatment of panic disorder - Clark, D; Ehlers, A (1993)
In recent years there has been a marked increase in research on the cognitive theory and treatment of panic. The present article provides an overview of this work. Following a brief description of the cognitive theory of panic, a series of experiments that were designed to test the theory are reported. The result of the experiments generally support the theory. The cognitive treatment of panic is then briefly described, followed by a review of relevant controlled trials. These trials suggest that cognitive therapy is an effective treatment for panic and that it compares favorably to some alternative behavioral and pharmacological treatments. © 1993 American Association of Applied and Preventive Psychology (AAAPP) All rights reserved.